Infectious disease dynamics: What characterizes a successful invader? - May, R; Gupta, S; Mclean, A (2001)
Against the background of human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) and other potentially emerging (or re-emerging) infectious diseases, this review will focus on the properties which enable an infectious agent to establish and maintain itself within a specified host population. We shall emphasize that for a pathogen to cross a species barrier is one thing, but for it successfully to maintain itself in the new population is must have a 'basic reproductive number', R(0), which satisfies R(0) > 1. We shall further discuss how behavioural factors interweave with the basic biology of the production of transmission stages by the pathogen, all subject to possible secular changes, to determine the magnitude of R(0). Although primarily focusing on HIV and AIDS, we shall review wider aspects of these questions.